Respuesta :
(2 − 3i) + (x + yi) = 6
We add the left hand side
(2+x) + (-3+y)i = 6
6 can be written in a+ib
6 can be written as 6 + 0i
(2+x) + (-3+y)i = 6 +0i
Now we frame 2 equations
2 + x= 6
-3 + y =0
Solve the first equation
2 + x = 6
Subtract 2 from both sides
x = 4
solve the second equation
-3 + y =0
Add 3 on both sides
y= 3
So x+yi is 4+3i
Answer:
x + yi = 4 + 3i
Step-by-step explanation:
Equation:
(2 − 3i) + (x + yi) = 6
Simple solution:
(2 − 3i) + (x + yi) = 6
= (2 − 3i) + (x + yi) - (2 − 3i) = 6 - (2 − 3i)
= x + yi = 6 - 2 +3i
= x + yi = 4 + 3i
= x + yi = 4 + 3i